Analisis Pengaruh Financing to Deposit Ratio (FDR) Terhadap Penempatan Dana Pada SBIS Bank Syariah di Indonesia - Supriono Supriono; Sri Herianingrum (Universitas Airlangga, 2017)
This study aimed to analyze the influence of Financing to Deposit Ratio (FDR) and to islamic banking fund placement in Islamic Certificate of Bank Indonesia Sharia (SBIS) in the period January 2009-December 2015. The research approach used is a quantitative technique of linear regression analysis. The dependent variable used is the placement of funds in SBIS, while the independent variables, Financing to Deposit Ratio (FDR). Determination of the number of samples using a non probability sampling methods saturated samples, the entire population sampled. The data used is secondary data. The regresion test results stating that the Financing to Deposit Ratio (FDR) significantly affects the placement of funds of islamic bank at SBIS in the period January 2009-December 2015.